Capital reallocation under climate policy uncertainty - Makram Khalil; Felix Strobel (Deutsche Bundesbank, 2023)
In a structural dynamic model that incorporates two broad production sectors with different carbon emissions, we find that climate policy uncertainty (CPU) shocks (i) lower the market value of the highly carbon-emitting sector relative to the low carbon-emitting sector, and (ii) reduce real investment and the capital stock in the highly carbon-emitting sector, while real investment in the sector with low carbon emissions tends to fare better. To apply the theoretical predictions to the data, we employ a news article-based measure of climate policy uncertainty to identify CPU shocks as well as quarterly balance sheet data of listed firms in the United States. In line with the predictions from the theoretical model, we find that in response to CPU shocks (i) financial markets markedly revalue strongly carbon-emitting firms relative to firms with low carbon emissions, and (ii) substantial investment reallocation takes place, in particular from the manufacturing sector towards services.
Keywords: E22; E44; Q54; Q58; 330; Climate policy uncertainty; production factor reallocation; firm-level investment decision; financial market valuation